2016
DOI: 10.1016/j.cyto.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade inflammation markers in children and adolescents: Influence of anthropometric characteristics and CRP and IL6 polymorphisms

Abstract: Overweight and obesity are associated with chronic and subclinical inflammation due to an imbalance of inflammatory mediators. However, the association with gene polymorphism has been rarely studied in children. The aim of this study was to determine if serum concentrations of C-reactive protein (CRP) and interleukin-6 (IL-6) are related to the IL6 rs1800795, IL6 rs2069845 and CRP rs1205 polymorphisms (SNPs) according to body mass index (BMI) in a sample of children and adolescents. A cross-sectional study in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 40 publications
2
19
0
2
Order By: Relevance
“…Our results are in agreement with prior studies that have consistently demonstrated an association between anthropometric measures of excess total and regional adiposity and CRP among both males and females and Hispanic‐only as well as multiethnic cohorts of children and adolescents ,. Body fat (%), by more direct measures (DXA and air displacement plethysmography), has also been significantly and positively associated with CRP among children and adolescents across studies ,, though Hispanic representation has been limited. In a study that estimated adiposity by both anthropometry and air displacement plethysmography, results were aligned with ours, though direct comparisons between BMI and body fat were not made.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in agreement with prior studies that have consistently demonstrated an association between anthropometric measures of excess total and regional adiposity and CRP among both males and females and Hispanic‐only as well as multiethnic cohorts of children and adolescents ,. Body fat (%), by more direct measures (DXA and air displacement plethysmography), has also been significantly and positively associated with CRP among children and adolescents across studies ,, though Hispanic representation has been limited. In a study that estimated adiposity by both anthropometry and air displacement plethysmography, results were aligned with ours, though direct comparisons between BMI and body fat were not made.…”
Section: Discussionsupporting
confidence: 92%
“…It is well known that such proteins are not only surrogate markers but are also directly involved in the pathophysiology of deleterious processes leading to end organ damage [18]. In children, other parameters are also found to linearly correlate with BMI and include blood polymorphonuclear count [19], IL-6, or CRP [20]. Hence, although the correlation coefficients between BMI and CP are not very strong, our data provide further support to our contention that BMI z-score in children may associate with later adverse events even among children whose body weight is within the normative range.…”
Section: Discussionmentioning
confidence: 99%
“…However, not only elderly pathologies are associated with the presence of low systemic inflammation. As systemic inflammation has also been reported in children and teenagers with weight problems [ 4 ], it is now clear that the persistence of the underlying condition and molecular mechanisms that trigger it should be taken into consideration in tandem with low chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%